The relationship between smartphone addiction, sleep quality and stress among university students - Faieza Samat; Minhalina Mokhtar; Suzaily Wahab (Pusat Pengurusan & Pembangunan Mahasiswa, Universiti Kebangsaan Malaysia, 2020)
This study investigated the relationship between smartphone addiction, sleep quality and stress level among university students. Questionnaires were distributed to 90 university students in year 2017 who were selected randomly from various residential colleges of the Universiti Kebangsaan Malaysia, Bangi Campus. The data were collected and analyzed using Statistical Package of Social Science (SPSS) software. The results showed that 41.4% of the students had high risk of smartphone addiction while 88.9% and 37.8% of them had poor sleep quality and high perceived stress respectively. It was also found that with confidence interval 90% and maximum error estimate 6%, there was a positive correlation between smartphone addiction and sleep quality. The highest correlation was between smartphone addiction level and perceived stress, while the least correlation was between sleep quality and perceived stress. Hence, it is suggested for the residential colleges to organize or uphold any relevant programs to reduce the smartphone addiction among university students.